Optimal choice and consumption of cost cap tariffs: Theory and empirical evidence - Philip Köhler; Jan Krämer; Lars Krüger (Business Research, 2014)
Cost cap tariffs are pay-per-use tariffs for which costs cannot exceed a predefined cost limit. They were recently introduced to telecommunications markets, but were previously also applied in the insurance industry as deductibles or in the rental industry as day rates. This paper develops and empirically validates a consumer surplus model that explains the optimal consumption pattern under cost cap tariffs and the conditions under which cost cap tariffs are chosen over pure pay-per-use and flat rate tariffs by a rational consumer. We find that cost cap tariffs are an optimal tariff choice only if the level of uncertainty is sufficiently high. Our theoretical predictions are supported by survey data.
Keywords: D11; D12; M31; 330; Tariff choice; Consumer surplus model; Cost cap tariff; Pay-per-use tariff; Flat rate tariff; Tariff bias; Service industries; Telecommunications; Tariff bias